Sylvanus Bourne papers - Bourne, Sylvanus, 1761-1817.
Correspondence, business and commercial papers, a scrapbook, and account books. Consists primarily of correspondence between Bourne and other American consular officers in European ports relating to commerce between the United States and European countries, primarily France and Great Britain. Also includes correspondence relating to United States foreign relations and politics, records concerning Bourne's business in Massachusetts, and family correspondence.
Correspondents include John Quincy Adams, Lawson Alexander, Richard Codman, George Rix Curtis, John Murray Forbes, Joseph Forman, George John Gregory, Levett Harris, James Maury, James C. Mountflorence, William Vans Murray, Joseph Pitcairn, Jacob Ridgway, J. Robertson, H. Rohan, Jonathan Russell, James Swan, David Bailie Warden, and William Worsdell.
In part, photocopies.
Massachusetts businessman, and U.S. consul in Santo Domingo, Dominican Republic (1790-1791) and Amsterdam, Netherlands (1794-1817).
Collection material in English and French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Alexander, Lawson -- Correspondence; Codman, Richard, -- 1762-1806 -- Correspondence; Curtis, George Rix -- Correspondence; Forbes, John Murray, -- 1771-1831 -- Correspondence; Forman, Joseph, -- active 1800 -- Correspondence; Gregory, George John -- Correspondence; Harris, Levett -- Correspondence; Maury, James, -- 1746-1840 -- Correspondence; Mountflorence, James C. -- Correspondence; Murray, William Vans, -- 1760-1803 -- Correspondence; Pitcairn, Joseph -- Correspondence; Ridgway, J. -- Correspondence; Robertson, J., -- active 1803 -- Correspondence; Rohan, H. -- Correspondence; Russell, Jonathan, -- 1771-1832 -- Correspondence; Swan, James, -- 1820-1895 -- Correspondence; Warden, David Bailie, -- 1772-1845 -- Correspondence; Worsdell, William -- Correspondence; Bourne family -- Correspondence; Diplomatic and consular service, American -- Netherlands; Diplomatic and consular service, American -- Santo Domingo (Dominican Republic); Europe -- Commerce -- United States; France -- Commerce -- United States; Great Britain -- Commerce -- United States; Massachusetts -- Commerce; United States -- Commerce -- History -- 19th century; United States -- Commerce -- Europe; United States -- Commerce -- France; United States -- Commerce -- Great Britain; United States -- Foreign relations -- 1783-1865.; United States -- Politics and government -- 1783-1865.; Businessmen; Diplomats